Ombra : supernatural music in the eighteenth century - McClelland, Clive; Lexington Books (yhtiö) (Lexington Books, 2013)
Ombra is the term which applies to an operatic scene involving the appearance of an oracle, a demon, witches, or ghosts. Such scenes can be traced back to the early days of opera and were commonplace in the seventeenth century in Italy and France. Operas based on the legends of Orpheus, Iphigenia, and Alcestis provide numerous examples of ombra and extend well into the eighteenth century.
Keywords: Hasse, Johann Adolph, : 1699-1783 : Cleofide; Jommelli, Niccolò, : 1714-1774 : Vologeso; Gluck, Christoph Willibald, : Ritter von, : 1714-1787 : Don Juan; Salieri, Antonio, : 1750-1825 : Grotta di Trofonio; Gazzaniga, Giuseppe, : 1743-1818 : Don Giovanni; Mozart, Wolfgang Amadeus, : 1756-1791 : Don Giovanni, : KV 527; Gluck, Christoph Willibald, : Ritter von, : 1714-1787 : Orfeo ed Euridice; Händel, Georg Friedrich, : 1685-1759 : Admeto, rè di Tessaglia, : HWV 22; Mozart, Wolfgang Amadeus, : 1756-1791 : Thamos, König in Ägypten, : KV 336a=345; 1700-luku; 1700-talet; Supernatural in opera; Opera : Europe : 18th century; musiikki; aiheet; paranormaalit ilmiöt; musiikkianalyysi; oopperat; musiikinhistoria; oopperataide; historia; yliluonnolliset olennot; uskonnollinen musiikki; musik; ämnen (områden); övernaturliga fenomen; musikanalys; operor (verk); musikhistoria; operakonst; övernaturliga väsen; religiös musik; Eurooppa; Europa